ZnO decorated laser-induced graphene produced by direct laser scribing - Rodrigues, Joana (2019)
A scalable laser scribing approach to produce zinc oxide (ZnO) decorated laser-induced graphene (LIG) in a unique laser-processing step was developed by irradiating a polyimide sheet covered with a Zn/ZnO precursor with a CO2 laser (10.6 μm) under ambient conditions. The laser scribing parameters revealed a strong impact on the surface morphology of the formed LIG, on ZnO microparticles' formation and distribution, as well as on the physical properties of the fashioned composites. The ZnO microparticles were seen to be randomly distributed along the LIG surface, with the amount and dimensions depending on the used laser processing conditions. Besides the synthesis conditions, the use of different precursors also resulted in distinct ZnO growth's yields and morphologies. Raman spectroscopy revealed the existence of both wurtzite-ZnO and sp2 carbon in the majority of the produced samples. Broad emission bands in the visible range and the typical ZnO near band edge (NBE) emission were detected by photoluminescence studies. The spectral shape of the luminescence signal was seen to be extremely sensitive to the employed processing parameters and precursors, highlighting their influence on the composites' optical defect distribution. The sample produced from the ZnO-based precursor evidenced the highest luminescence signal, with a dominant NBE recombination. Electrochemical measurements pointed to the existence of charge transfer processes between LIG and the ZnO particles.